Composite phase change material for temperature control of drilling fluid and preparation method of composite phase change material
Through the composite phase change material of expanded graphite and modified normal alkane, the problems of insufficient phase change temperature and complex preparation in the prior art are solved, and high-efficiency and low-cost temperature control of natural gas hydrate formation drilling fluid is achieved to ensure the well wall Stability and thermal stability.
Patent Information
- Application Number
- CN202310786650.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
The phase transition temperature of the existing temperature-controlled materials for natural gas hydrate drilling fluid cannot meet the formation needs, and the preparation process is complex and costly, so it cannot achieve on-site application.
Expanded graphite and modified normal alkanes are used as composite phase change materials. By controlling its weight ratio and preparation process, the latent heat and stability of the phase change are optimized, and composite phase change materials that meet the temperature control requirements of natural gas hydrate formation drilling fluid are prepared.
A composite phase change material with high phase change latent heat is achieved, which meets the drilling temperature requirements of natural gas hydrate formations, has low cost and simple preparation technology, has good thermal stability and temperature control effect, and can effectively inhibit hydrate decomposition and wellbore hydrate Regenerate.
Smart Images

Figure CN119220227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of drilling fluid for natural gas hydrate drilling, and in particular to a composite phase change material for drilling fluid temperature control and a preparation method thereof, and in particular to a composite phase change material for natural gas hydrate formation drilling fluid temperature control. Background Art
[0002] During the drilling process of hydrate reservoirs, the friction between the drill bit, drilling fluid and formation rock will generate heat in the horizontal well section, causing the drilling fluid to heat up. When the temperature is higher than the formation hydrate phase equilibrium temperature, it will cause hydrate decomposition and affect the stability of the wellbore. In order to solve this problem, intelligent temperature control materials with a temperature similar to that of the hydrate reservoir are usually added to the drilling fluid. During the cooling process from the wellhead to the seabed, phase change is used to store cold, and the cold is released in the horizontal well section to balance the heat generated by friction and other effects, thereby controlling the temperature rise of the drilling fluid. During the process of returning to the deepwater low-temperature wellbore, heat is released through phase change, reducing the supercooling of the wellbore hydrate regeneration and inhibiting the formation of hydrates in the wellbore. Existing phase change temperature control materials for drilling fluids are usually used in high-temperature formations and are not suitable for the temperature requirements of natural gas hydrate formation drilling. The currently disclosed pilot process of temperature-control microcapsules for natural gas hydrates is very complicated, the raw materials are expensive, and it is impossible to achieve field application.
[0003] CN111894520A discloses a method for regulating the temperature of drilling fluid based on paraffin materials. By adding phase-change paraffin with a particle size range of 0.2-0.3 mm in the drilling fluid, using phase-change paraffin with a phase-change temperature of 60°C-180°C and a phase-change latent heat of 140-200 J / g, the microencapsulated paraffin is dispersed in the drilling fluid. The phase-change paraffin material has a high phase-change latent heat, and the phase-change latent heat loss is small after repeated phase-change processes, so that the drilling fluid system has the characteristics of high-temperature cooling. The drilling fluid is cooled by the properties of the phase-change paraffin material itself, and the raw materials of the phase-change material drilling fluid system are easy to obtain and low in cost, and have good compatibility with conventional drilling fluid admixtures, and are convenient for on-site construction. However, the phase-change latent heat of the microencapsulated phase-change material has not been tested, and the phase-change temperature cannot meet the temperature requirements for natural gas hydrate formation drilling.
[0004] CN113249097A discloses a polyacrylate phase-change microcapsule and a preparation method thereof. The polyacrylate phase-change microcapsule is prepared by suspension polymerization, with a low-melting-point phase-change material as the capsule core and a polyacrylate modified with an anti-ultraviolet absorber as the capsule wall. An organic anti-ultraviolet-modified polyacrylate wall material is obtained by polymerizing an organic anti-ultraviolet absorber containing an unsaturated double bond with an acrylate monomer, and the organic anti-ultraviolet absorber is fixed in the capsule wall through a double bond reaction, giving the microcapsule wall an excellent ultraviolet shielding function. When the external temperature changes, the coated phase-change material absorbs or releases a large amount of heat through phase transition, so that the microcapsule has a better temperature control effect. Although the microcapsule has a good coating effect, and the phase change enthalpy value of repeated experiments is 109.2-176.1J / g, a large amount of volatile organic matter remains on the surface of the wall material, which brings many safety hazards to practical applications. At the same time, the phase change temperature of the microcapsule cannot be applied to natural gas hydrate formation drilling.
[0005] CN115160993A discloses a temperature-controlling microcapsule for natural gas hydrates, its preparation method and application, and water-based drilling fluid. With nano-silicon dioxide as the wall material and tetrabutylammonium bromide as the core material, a phase-change temperature-controlling microcapsule is prepared, with a phase-change temperature of 10-13°C, a phase-change latent heat of 100-130 J / g, and a coverage rate of more than 60%. The temperature-controlling microcapsule has a low phase-change temperature, good temperature control performance, good drilling fluid compatibility, can store and release cold energy through phase change, maintain the stability of the hydrate formation temperature, inhibit hydrate decomposition, effectively ensure the stability of the well wall, and show good thermal stability. In addition, it also has certain viscosity-increasing and filtration loss reduction effects. However, the raw materials of this product are expensive, the pilot process is complicated, and the phase-change latent heat needs to be further improved.
[0006] Therefore, it is of great significance to research and develop a new composite phase change material for drilling fluid temperature control with high phase change latent heat, low cost and simple preparation process, especially a new composite phase change material for drilling fluid temperature control in natural gas hydrate formations. Summary of the invention
[0007] In order to solve the problems of the prior art, the purpose of the present invention is to provide a composite phase change material for drilling fluid temperature control and a preparation method thereof. The composite phase change material for drilling fluid temperature control has high phase change latent heat and can be used for natural gas hydrate formation drilling fluid temperature control. Furthermore, the preparation method of the composite phase change material for drilling fluid temperature control has the advantages of low cost and simple preparation process.
[0008] To achieve the above objectives, in a first aspect, the present invention provides a composite phase change material for drilling fluid temperature control, comprising expanded graphite and a phase change component adsorbed in the expanded graphite, wherein the phase change component comprises modified normal alkane.
[0009] Compared with the existing temperature control materials for drilling fluid, the composite phase change material of the present invention has high phase change latent heat, and both the melting enthalpy and the solidification enthalpy are greater than 200 J / g. The phase change temperature of the composite phase change material meets the requirements for natural gas hydrate formation drilling.
[0010] As a specific embodiment of the present invention, preferably, the weight ratio of the expanded graphite to the modified normal alkane is (5-20):1, and more preferably (5-10):1.
[0011] In the composite phase change material of the present invention, by controlling the mixing ratio of expanded graphite and modified normal alkane, the phase change latent heat of the composite phase change material can be optimized, and the overflow of the core modified normal alkane can be effectively prevented to cause the composite phase change material to fail. When the weight ratio of the expanded graphite to the modified normal alkane is (5-20):1, a higher phase change latent heat can be obtained, the temperature control effect can be better exerted, and the stability of the composite phase change material can be ensured; further, when the weight ratio of the expanded graphite to the modified normal alkane is (5-10):1, a higher phase change latent heat can be obtained, the temperature control effect can be better exerted, and the stability of the composite phase change material can be ensured.
[0012] As a specific embodiment of the present invention, preferably, the expanded graphite is made of expandable graphite by high-temperature expansion. Further preferably, the conditions of the high-temperature expansion are: temperature 840-860°C, time 20-40s; and / or the expandable graphite is at least one of flake, spherical, and worm-shaped; and / or the expansion rate of the expandable graphite is greater than 300mL / g.
[0013] As a specific embodiment of the present invention, preferably, the modified normal alkane is made of fatty acid ester modified normal alkane, and further preferably, the normal alkane is n-tetradecane and n-hexadecane, preferably the weight ratio of the two is (1-3): (1-5); and / or, the modification conditions include: temperature of 40-65°C, time of 8-12h, and stirring rate of 200-400r / min.
[0014] The present invention has found through research that a new phase change material suitable for hydrate formation drilling temperature can be obtained by modifying and compounding normal alkanes with fatty acid esters.
[0015] The present invention has found through research that n-tetradecane and n-hexadecane in normal alkanes have good phase change latent heat performance and suitable phase change temperature. The normal alkanes modified by fatty acid esters are suitable for composite phase change materials for drilling fluid temperature control, especially for natural gas hydrate formation drilling fluid temperature control.
[0016] As a specific embodiment of the present invention, preferably, the modification of the modified normal alkane includes the following steps: mixing the normal alkane with fatty acid ester and then adding a nucleating agent and a binder to obtain the modified normal alkane; further preferably, mixing n-tetradecane and n-hexadecane with fatty acid ester in a weight ratio of (1-3):(1-5):1, and further preferably 1:(2-4):1; and / or the amount of the nucleating agent added is 1-5% of the mass of the modified normal alkane, preferably 2-3%; and / or the amount of the binder added is 2-6% of the mass of the modified normal alkane, preferably 3-4%.
[0017] As a specific embodiment of the present invention, preferably, the phase change component further comprises nano copper and / or nano silicon dioxide;
[0018] Further preferably, the particle size of the nano copper is 10-100 nm, preferably 20-40 nm; and / or, the amount of the nano copper added is 0.2-3% of the mass of the modified normal alkane, preferably 0.5-1.5%; and / or
[0019] Further preferably, the particle size of the nano-silicon dioxide is 10-200 nm, preferably 20-150 nm; and / or the added amount of the nano-silicon dioxide is 2-10% of the mass of the modified normal alkane, preferably 3-6%.
[0020] In the composite phase change material of the present invention, after the introduction of nano copper, the composite phase change material has good thermal conductivity; after the introduction of hydrophilic nano silicon dioxide, the composite phase change material exhibits hydrophilicity; and the composite phase change material has excellent thermal stability. After 30 cycles, the melting enthalpy and solidification enthalpy reduction rates of the composite phase change material are 3.5% and 3.2%.
[0021] As a specific embodiment of the present invention, preferably, the median particle size of the composite phase change material is 1-50 μm, preferably 10-30 μm; and / or
[0022] The phase change temperature of the composite phase change material is 6-18°C, preferably 12-18°C; and / or
[0023] The phase change latent heat of the composite phase change material is 100-230 J / g, preferably 160-220 J / g; and / or
[0024] The coverage rate of the composite phase change material is 10-80%, preferably 55-75%.
[0025] To achieve the above objectives, in a second aspect, the present invention provides a method for preparing the above-mentioned composite phase change material for drilling fluid temperature control, comprising the following steps: adsorbing and mixing modified normal alkane and expanded graphite, and then washing, filtering and drying to obtain a composite phase change material.
[0026] As a specific embodiment of the present invention, preferably, the adsorption mixing conditions include: temperature 60-70°C, time 3-5h, stirring rate 200-400r / min; and / or, the washing adopts 50wt%~75wt% ethanol solution; and / or, the drying conditions include: temperature 30-50°C, time 12-20h.
[0027] As a specific embodiment of the present invention, preferably, the preparation method comprises the following steps:
[0028] S1, adding nano copper to modified normal alkane and performing first ultrasonic mixing to obtain a suspension;
[0029] S2, melting and mixing the suspension obtained in step S1 with expanded graphite to obtain a composite phase change material intermediate;
[0030] S3, adding nano-silicon dioxide into modified normal alkane and performing a second ultrasonic mixing to obtain a composite sol;
[0031] S4, adding the composite phase change material intermediate to the composite sol obtained in step S3 and mixing them, and after the composite phase change material intermediate absorbs the composite sol, washing, filtering and drying are performed to obtain the composite phase change material.
[0032] As a specific embodiment of the present invention, preferably, in step S1, the first ultrasonic mixing time is 10-60 min, preferably 20-40 min; and / or,
[0033] In step S2, the melt mixing step comprises: mixing the suspension and expanded graphite uniformly and then placing in a vacuum drying oven, solidifying the modified normal alkane in the suspension at 2-8°C, and then heating to 40-60°C and stabilizing for 4-8h to obtain the composite phase change material intermediate; and / or,
[0034] In step S2, the weight ratio of the suspension to the expanded graphite is 6-12:1, preferably 8-10:1; and / or,
[0035] In step S3, the second ultrasonic mixing time is 10-60 min, preferably 20-40 min; and / or,
[0036] In step S4, the mixing conditions include: temperature 60-70°C, time 3-5h, and stirring rate 200-400r / min.
[0037] Through the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0038] (1) Compared with other temperature control materials for drilling fluid, the composite phase change material for drilling fluid temperature control provided by the present invention has a phase change temperature that meets the requirements for natural gas hydrate formation drilling, a high phase change latent heat, and a melting enthalpy and a solidification enthalpy that are both greater than 200 J / g; further, after introducing nano-copper and being modified by hydrophilic nano-silicon dioxide, the composite phase change material has good thermal conductivity and is hydrophilic; it has excellent thermal stability, and after 30 cycles, the melting enthalpy and solidification enthalpy reduction rates of the composite phase change material are 3.5% and 3.2%.
[0039] (2) The composite phase change material for drilling fluid temperature control provided by the present invention cools down from the wellhead to the seabed and stores cold through phase change, and then releases the cold in the horizontal well section of the reservoir to control the increase in drilling fluid temperature and prevent decomposition of reservoir hydrates. Returning from the horizontal well section to the deep-water wellbore is a cooling process. The composite phase change material releases heat through phase change to control the decrease in drilling fluid temperature to prevent the regeneration of hydrates in the wellbore, and has a "double-effect" effect of inhibiting the decomposition of formation hydrates and the regeneration of low-temperature wellbore hydrates.
[0040] (3) The composite phase change material for drilling fluid temperature control provided by the present invention has good compatibility with drilling fluid. When 5wt% of the composite phase change material is added, the apparent viscosity of the drilling fluid increases by 10.4%, the plastic viscosity increases by 12.5%, and the dynamic-plastic ratio is 0.58, which does not cause flow obstruction but is conducive to carrying cuttings and cleaning the wellbore; at the same time, the filtration loss reduction rate is 20%, which is of great significance for maintaining the stability of the wellbore wall of the hydrate formation.
[0041] (4) In addition, the composite phase change material for drilling fluid temperature control provided by the present invention has a simple preparation process, cheap raw materials, is environmentally friendly and non-toxic, and is easy to commercialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 DSC spectra of modified n-alkanes (MNA) and composite phase change materials (PCM);
[0043] Figure 2 DSC spectra of the composite phase change material after 1, 10, 20 and 30 thermal cycles;
[0044] Figure 3 This is the test curve of temperature control performance for simulating hydrate reservoir conditions;
[0045] Figure 4 It is the test curve of temperature control performance simulating wellbore conditions;
[0046] Figure 5 The rheology of drilling fluid with or without composite phase change material;
[0047] Figure 6 It is the filtration loss of drilling fluid with or without composite phase change materials. DETAILED DESCRIPTION
[0048] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0049] A first aspect of the present invention provides a composite phase change material for drilling fluid temperature control, wherein the raw materials of the composite phase change material include a phase change core material and a wall material; wherein the phase change core material is modified normal alkane, and the wall material is expanded graphite.
[0050] According to the present invention, the composite phase change material for controlling the temperature of drilling fluid is formed by the wall material expanded graphite through the capillary force to adsorb the core material modified normal alkane.
[0051] According to the present invention, preferably, the phase change core material modified normal alkane is prepared by mixing n-tetradecane, n-hexadecane and fatty acid ester, and the weight ratio of n-tetradecane: n-hexadecane: fatty acid ester is (1-3): (1-5): 1, preferably n-tetradecane: n-hexadecane: fatty acid ester is 1: (2-4): 1.
[0052] According to the present invention, preferably, the expanded graphite is prepared by high-temperature expansion of expandable graphite.
[0053] According to the present invention, preferably, the weight ratio of the core material: the wall material is (5-20): 1, preferably (5-10): 1; in the composite phase change material for drilling fluid temperature control, by controlling the mixing ratio of the wall material expanded graphite and the core material modified normal alkane, the phase change latent heat of the composite phase change material can be optimized, and the overflow and failure of the core material can be effectively prevented.
[0054] According to the present invention, preferably, the median particle size of the new composite phase change material for drilling fluid temperature control is 1-50 μm, preferably 10-30 μm.
[0055] According to the present invention, preferably, the phase change temperature of the composite phase change material is 6-18°C, preferably 12-18°C; the composite phase change material for drilling fluid temperature control requires the phase change temperature to meet the natural gas hydrate formation drilling temperature requirement.
[0056] According to the present invention, preferably, the phase change latent heat of the composite phase change material is 100-230 J / g, preferably 160-220 J / g; the higher the phase change latent heat of the composite phase change material for drilling fluid temperature control, the better the temperature regulating effect can be played in the horizontal well section drilling of the natural gas hydrate formation and the seabed low-temperature wellbore circulation section. In the cooling process from the wellhead to the seabed, phase change stores cold, and releases cold in the horizontal well section to balance the heat generated by friction and other effects, thereby controlling the temperature rise of the drilling fluid; in the process of returning to the deep-water low-temperature wellbore, heat is released through phase change, the supercooling of the wellbore hydrate regeneration is reduced, and the hydrate formation in the wellbore is inhibited.
[0057] According to the present invention, preferably, the coverage of the composite phase change material is 10-80%, preferably 55-75%; wherein the coverage is calculated by the ratio of the latent heat of phase change of the composite phase change material to the latent heat of phase change of the core material. The composite phase change material for drilling fluid temperature control has a high coverage, indicating that the composite phase change material has a high latent heat of phase change, and the core material will not overflow from the wall material and fail.
[0058] A second aspect of the present invention provides a method for preparing the aforementioned composite phase change material, comprising the following steps:
[0059] (1) mixing n-tetradecane, n-hexadecane and fatty acid ester, and adding a nucleating agent and a binder to obtain modified n-alkane;
[0060] (2) slowly adding nano-copper into modified normal alkane for a second mixing, and ultrasonically dispersing to obtain a uniformly dispersed nano-copper / modified normal alkane suspension;
[0061] (3) Optionally, the expandable graphite is placed in a drying oven for drying, and then placed in a muffle furnace for expansion to obtain expanded graphite;
[0062] (4) performing a third mixing of the liquid phase and expanded graphite, and melt mixing to obtain a modified normal alkane / expanded graphite composite phase change material;
[0063] (5) adding nano-silicon dioxide to the modified normal alkane for a fourth mixing, and ultrasonically dispersing to obtain a composite sol;
[0064] (6) adding the modified normal alkane / expanded graphite composite phase change material into the composite sol for fifth mixing, and after sufficient adsorption, washing, filtering and drying are performed to obtain the composite phase change material.
[0065] According to the present invention, in step (1), preferably, the amount of nucleating agent added is 1-5% by mass of the modified normal alkane, preferably 2-3%; preferably, the amount of binder added is 2-6% by mass of the modified normal alkane, preferably 3-4%.
[0066] According to the present invention, in step (1), preferably, the first mixing conditions include: temperature of 40-65°C, time of 8-12h, and stirring rate of 200-400r / min.
[0067] According to the present invention, in step (1), the modified normal alkane obtained by the first mixing is the phase change core material in the preparation method provided by the present invention.
[0068] According to the present invention, in step (2), preferably, the nano copper particle size is 10-100 nm, preferably 20-40 nm; the added amount is 0.2-3% of the mass of the modified normal alkane, preferably 0.5-1.5%.
[0069] According to the present invention, in step (2), preferably, the second mixing ultrasonic dispersion time is 10-60 min, preferably 20-40 min.
[0070] According to the present invention, in step (3), the expandable graphite is in at least one of the following forms: flake, spherical, and worm-like.
[0071] According to the present invention, in step (3), the expansion conditions of expandable graphite include: expansion temperature of 840-860° C., and expansion time of 20-40 s.
[0072] According to the present invention, in step (3), the expansion ratio of the expandable graphite (expanded graphite volume / mass) is greater than 300 mL / g.
[0073] According to the present invention, in step (3), the expanded graphite is used as the wall material in the preparation method provided by the present invention.
[0074] According to the present invention, in step (4), there is no particular limitation on the mixing method of the third mixing, as long as the core material and the wall material can be fully blended to form a uniform dispersed phase.
[0075] According to the present invention, in step (4), the preparation method of the modified normal alkane / expanded graphite composite phase change material comprises: placing the mixture into a vacuum drying oven after being fully mixed, adjusting the temperature to 2-8°C to fully solidify the modified normal alkane, and continuing to heat the mixture to 40-60°C and stabilizing the mixture for 4-8 hours to obtain the modified normal alkane / expanded graphite composite phase change material.
[0076] According to the present invention, in step (5), preferably, the nano-silicon dioxide particle size is 10-200 nm, preferably 20-150 nm; the added amount is 2-10% of the mass of the modified normal alkane, preferably 3-6%.
[0077] According to the present invention, in step (5), preferably, the fourth mixing ultrasonic dispersion time is 10-60 min, preferably 20-40 min.
[0078] According to the present invention, in step (6), preferably, the fifth mixing conditions include: temperature 60-70°C, time 3-5h, and stirring rate 200-400r / min.
[0079] According to the present invention, in step (6), the washing preferably uses a 50% ethanol solution.
[0080] According to the present invention, in step (6), there is no particular limitation on the filtration, and conventional solid-liquid separation methods can be used.
[0081] According to the present invention, in step (6), preferably, the drying conditions include: temperature of 30-50° C. and time of 12-20 h.
[0082] The present invention is described in detail below by way of examples.
[0083] 1. Raw materials
[0084] Nucleating agents and binders were purchased from Dongying Shida Innovation Technology Co., Ltd.
[0085] (II) Measurement method
[0086] The median particle size was measured by laser particle size analyzer;
[0087] The phase transition temperature was determined by differential scanning calorimetry;
[0088] The latent heat of phase change was measured by differential scanning calorimetry.
[0089] Example 1
[0090] n-tetradecane, n-hexadecane and fatty acid ester are first mixed in a weight ratio of 1:3:1 (stirring speed is 300 r / min, temperature is 50° C., and time is 10 h), and 2 wt % of nucleating agent and 3 wt % of binder are added based on the mass of modified n-alkane as 100% to obtain modified n-alkane;
[0091] Slowly adding 1 wt% nano copper (20-40 nm) into the modified normal alkane for a second mixing, and ultrasonically dispersing for 30 min to obtain a uniformly dispersed nano copper / modified normal alkane suspension;
[0092] The expandable graphite was placed in a drying oven for drying, and then placed in a muffle furnace for expansion to obtain expanded graphite (expansion temperature was 850°C, and expansion time was 30s);
[0093] The suspension is mixed with expanded graphite for a third time (the weight ratio of the two is 8:1), and the temperature is first lowered to 4° C. in a vacuum drying oven to fully solidify the modified normal alkane, and then the temperature is raised to 50° C. and stabilized for 6 hours to fully adsorb the expanded graphite, thereby obtaining a modified normal alkane / expanded graphite composite phase change material;
[0094] Adding 5 wt % of nano-silicon dioxide (20-100 nm) to the modified normal alkane for a fourth mixing, and ultrasonically dispersing for 30 minutes to obtain a composite sol;
[0095] The modified normal alkane / expanded graphite composite phase change material was added to the composite sol for the fifth mixing (stirring speed of 300 r / min, temperature of 65°C, time of 4 h). After sufficient adsorption, it was washed with 50wt% ethanol solution, filtered and placed in a drying oven at 40°C for 16 h to obtain a composite phase change material.
[0096] The phase change temperature, phase change latent heat and coverage of Example S1 are shown in Table 1.
[0097] Example 2
[0098] n-tetradecane, n-hexadecane and fatty acid ester are first mixed in a weight ratio of 1:3:1 (stirring speed is 300 r / min, temperature is 60° C., and time is 10 h), and 3 wt % of nucleating agent and 3 wt % of binder are added based on the mass of modified n-alkane as 100% to obtain modified n-alkane;
[0099] Slowly adding 1 wt% nano copper (20-40 nm) into the modified normal alkane for a second mixing, and ultrasonically dispersing for 30 min to obtain a uniformly dispersed nano copper / modified normal alkane suspension;
[0100] The expandable graphite was placed in a drying oven for drying, and then placed in a muffle furnace for expansion to obtain expanded graphite (expansion temperature was 850°C, and expansion time was 30s);
[0101] The suspension is mixed with expanded graphite for a third time (the weight ratio of the two is 10:1), and the temperature is firstly lowered to 2°C in a vacuum drying oven to fully solidify the modified normal alkane, and then the temperature is raised to 50°C and stabilized for 6 hours to fully adsorb the expanded graphite, thereby obtaining a modified normal alkane / expanded graphite composite phase change material;
[0102] Adding 5 wt % of nano-silicon dioxide (20-100 nm) to the modified normal alkane for a fourth mixing, and ultrasonically dispersing for 30 minutes to obtain a composite sol;
[0103] The modified normal alkane / expanded graphite composite phase change material was added to the composite sol for the fifth mixing (stirring speed of 300 r / min, temperature of 65°C, time of 5 h). After sufficient adsorption, it was washed with 50wt% ethanol solution, filtered and placed in a drying oven at 40°C for 16 h to obtain a composite phase change material.
[0104] The phase change temperature, phase change latent heat and coverage results of Example S2 are shown in Table 1.
[0105] Example 3
[0106] n-tetradecane, n-hexadecane and fatty acid ester are first mixed in a weight ratio of 1:3:1 (stirring speed is 300 r / min, temperature is 60° C., and time is 12 h), and 2 wt % of nucleating agent and 4 wt % of binder are added based on the mass of modified n-alkane as 100% to obtain modified n-alkane;
[0107] Slowly adding 1 wt% nano copper (20-40 nm) into the modified normal alkane for a second mixing, and ultrasonically dispersing for 40 min to obtain a uniformly dispersed nano copper / modified normal alkane suspension;
[0108] The expandable graphite was placed in a drying oven for drying, and then placed in a muffle furnace for expansion to obtain expanded graphite (expansion temperature was 850°C, and expansion time was 30s);
[0109] The suspension is mixed with expanded graphite for a third time (the weight ratio of the two is 8:1), and the mixture is first cooled to 2° C. in a vacuum drying oven to fully solidify the modified normal alkane, and then heated to 50° C. and stabilized for 6 hours to fully adsorb the expanded graphite, thereby obtaining a modified normal alkane / expanded graphite composite phase change material;
[0110] Adding 5 wt % of nano-silicon dioxide (20-100 nm) to the modified normal alkane for a fourth mixing, and ultrasonically dispersing for 40 min to obtain a composite sol;
[0111] The modified normal alkane / expanded graphite composite phase change material was added to the composite sol for the fifth mixing (stirring speed of 300 r / min, temperature of 65°C, time of 5 h). After sufficient adsorption, it was washed with 50wt% ethanol solution, filtered and placed in a drying oven at 40°C for 16 h to obtain a composite phase change material.
[0112] The phase change temperature, phase change latent heat and coverage of Example S3 are shown in Table 1.
[0113] Example 4
[0114] n-tetradecane, n-hexadecane and fatty acid ester are first mixed in a weight ratio of 1:3:1 (stirring speed is 400 r / min, temperature is 60° C., and time is 10 h), and 2 wt % of nucleating agent and 3 wt % of binder are added based on the mass of modified n-alkane as 100% to obtain modified n-alkane;
[0115] Slowly adding 1 wt% nano copper (20-40 nm) into the modified normal alkane for a second mixing, and ultrasonically dispersing for 30 min to obtain a uniformly dispersed nano copper / modified normal alkane suspension;
[0116] The expandable graphite was placed in a drying oven for drying, and then placed in a muffle furnace for expansion to obtain expanded graphite (expansion temperature was 850°C, and expansion time was 30s);
[0117] The suspension is mixed with expanded graphite for a third time (the weight ratio of the two is 8:1), and the temperature is firstly lowered to 4°C in a vacuum drying oven to fully solidify the modified normal alkane, and then the temperature is raised to 50°C and stabilized for 8 hours to fully adsorb the expanded graphite, thereby obtaining a modified normal alkane / expanded graphite composite phase change material;
[0118] Adding 5 wt % of nano-silicon dioxide (20-100 nm) to the modified normal alkane for a fourth mixing, and ultrasonically dispersing for 30 minutes to obtain a composite sol;
[0119] The modified normal alkane / expanded graphite composite phase change material was added to the composite sol for the fifth mixing (stirring speed of 400 r / min, temperature of 65°C, time of 4 h). After sufficient adsorption, it was washed with 50wt% ethanol solution, filtered and placed in a drying oven at 40°C for 16 h to obtain a composite phase change material.
[0120] The phase change temperature, phase change latent heat and coverage of Example S4 are shown in Table 1.
[0121] Table 1
[0122]
[0123]
[0124] Test Case
[0125] The performance of the new composite phase change material for temperature control of natural gas hydrate formation drilling fluid prepared in Example 1 was tested.
[0126] Latent heat properties and thermal stability of composite phase change materials
[0127] like Figure 1 and 2As shown in the figure, the melting enthalpy of modified normal alkane (MNA) is 260.3 J / g, and the solidification enthalpy is 260.1 J / g, and the melting enthalpy of the composite phase change material (PCM) is 191.4 J / g, and the solidification enthalpy is 190.6 J / g, indicating that it has excellent phase change latent heat performance; at the same time, after 30 cycles, the melting enthalpy and solidification enthalpy reduction rates of the composite phase change material are 3.3% and 3.1% respectively, indicating that the composite phase change material has good thermal stability.
[0128] Temperature Control Performance of Composite Phase Change Materials
[0129] The temperature of the thermostat was lowered to 3°C to simulate the low-temperature environment of the seabed, so that the phase change material could store cold energy, and then the temperature was raised to 15°C to simulate the hydrate reservoir; at the same time, the heating stirrer was turned on to simulate the heat release of underground cutting. Figure 3 It can be seen that after reaching the phase change temperature, the composite phase change material solution can effectively control the solution temperature rise, and when the amount is 5wt%, the maximum temperature can be reduced by 2.1℃. Subsequently, the temperature is raised to 18℃ to simulate the cutting temperature rise process of the horizontal well section of the reservoir, and then cooled to 3℃ for a period of time to simulate the seabed temperature. Figure 4 It can be seen that the lowest temperature of the solution with 5wt% of the composite phase change material added is 2.8°C higher than that of the solution without the composite phase change material. In summary, the composite phase change material has good temperature control performance, which can simultaneously control the increase of the drilling fluid temperature in the horizontal section of the reservoir and the decrease of the drilling fluid temperature at the bottom of the wellbore, inhibiting the decomposition of reservoir hydrates and the regeneration of wellbore hydrates.
[0130] Drilling fluid compatibility of composite phase change materials
[0131] Figure 5 and 6 The effect of 5wt% composite phase change material on the rheology and filtration of drilling fluid is shown. The results show that the addition of phase change material increases the viscosity of drilling fluid, with the apparent viscosity increasing by 10.2%, the plastic viscosity increasing by 12.2%, and the dynamic-plastic ratio being 0.56. It does not cause flow obstacles, but is conducive to carrying cuttings and cleaning the wellbore. At the same time, the addition of 5wt% composite phase change material can reduce the filtration loss of drilling fluid by 1.1mL, with a reduction rate of 22%, which is of great significance for maintaining the stability of the wellbore wall of the hydrate formation. In summary, the composite phase change material has good compatibility with the drilling fluid.
[0132] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite phase change material for drilling fluid temperature control, characterized in that: The invention comprises expanded graphite and a phase change component adsorbed in the expanded graphite, wherein the phase change component comprises modified normal alkane.
2. The composite phase change material according to claim 1, characterized in that: The weight ratio of the expanded graphite to the modified normal alkane is (5-20):1, preferably (5-10):
1.
3. The composite phase change material according to claim 1 or 2, characterized in that: The expanded graphite is made of expandable graphite by high-temperature expansion. Preferably, the conditions for the high-temperature expansion are: temperature 840-860° C., time 20-40 s; and / or the expandable graphite is at least one of flake, spherical, and worm-shaped; and / or the expansion rate of the expandable graphite is greater than 300 mL / g.
4. The composite phase change material according to any one of claims 1 to 3, characterized in that: The modified normal alkane is made from normal alkane modified by fatty acid esters. Preferably, the normal alkane is n-tetradecane and n-hexadecane, and preferably the weight ratio of the two is (1-3): (1-5); and / or, the modification conditions include: temperature of 40-65°C, time of 8-12h, and stirring rate of 200-400r / min.
5. The composite phase change material according to any one of claims 1 to 4, characterized in that: The modification of the modified normal alkane comprises the following steps: after mixing the normal alkane with fatty acid ester, a nucleating agent and a binder are added to obtain the modified normal alkane; preferably, n-tetradecane and n-hexadecane are mixed with the fatty acid ester in a weight ratio of (1-3):(1-5):1, more preferably 1:(2-4):1; and / or the amount of the nucleating agent added is 1-5% of the mass of the modified normal alkane, preferably 2-3%; and / or the amount of the binder added is 2-6% of the mass of the modified normal alkane, preferably 3-4%.
6. The composite phase change material according to any one of claims 1 to 5, characterized in that: The phase change component also includes nano copper and / or nano silicon dioxide; Preferably, the particle size of the nano copper is 10-100 nm, preferably 20-40 nm; and / or, the amount of the nano copper added is 0.2-3% of the mass of the modified normal alkane, preferably 0.5-1.5%; and / or Preferably, the particle size of the nano-silicon dioxide is 10-200 nm, preferably 20-150 nm; and / or, the amount of the nano-silicon dioxide added is 2-10% of the mass of the modified normal alkane, preferably 3-6%.
7. The composite phase change material according to any one of claims 1 to 6, characterized in that: The median particle size of the composite phase change material is 1-50 μm, preferably 10-30 μm; and / or The phase change temperature of the composite phase change material is 6-18°C, preferably 12-18°C; and / or The phase change latent heat of the composite phase change material is 100-230 J / g, preferably 160-220 J / g; and / or The coverage rate of the composite phase change material is 10-80%, preferably 55-75%.
8. A method for preparing a composite phase change material for temperature control of drilling fluid according to any one of claims 1 to 7, characterized in that: The following steps are involved: The modified normal alkane is adsorbed and mixed with expanded graphite, and then washed, filtered and dried to obtain a composite phase change material; Preferably, the adsorption mixing conditions include: temperature 60-70°C, time 3-5h, stirring rate 200-400r / min; and / or, the washing adopts 50wt%~75wt% ethanol solution; and / or, the drying conditions include: temperature 30-50°C, time 12-20h.
9. The preparation method according to claim 8, characterized in that: The preparation method comprises the following steps: S1, adding nano copper to modified normal alkane and performing first ultrasonic mixing to obtain a suspension; S2, melting and mixing the suspension obtained in step S1 with expanded graphite to obtain a composite phase change material intermediate; S3, adding nano-silicon dioxide into modified normal alkane and performing a second ultrasonic mixing to obtain a composite sol; S4, adding the composite phase change material intermediate to the composite sol obtained in step S3 and mixing them, and after the composite phase change material intermediate absorbs the composite sol, washing, filtering and drying are performed to obtain the composite phase change material.
10. The preparation method according to claim 9, characterized in that: In step S1, the first ultrasonic mixing time is 10-60 min, preferably 20-40 min; and / or, In step S2, the melt mixing step comprises: mixing the suspension and expanded graphite uniformly and then placing in a vacuum drying oven, solidifying the modified normal alkane in the suspension at 2-8°C, and then heating to 40-60°C and stabilizing for 4-8h to obtain the composite phase change material intermediate; and / or, In step S2, the weight ratio of the suspension to the expanded graphite is 6-12:1, preferably 8-10:1; and / or, In step S3, the second ultrasonic mixing time is 10-60 min, preferably 20-40 min; and / or, In step S4, the mixing conditions include: temperature 60-70°C, time 3-5h, and stirring rate 200-400r / min.
Citation Information
Cited By
High-thermal-conductivity glass fiber reinforced phase change laminated plate and preparation method thereof
CN120756156A
